Adiponectin regulates proliferation and differentiation of chicken skeletal muscle satellite cells via ERK1/2 and p38 signaling pathways - Liping Guo; Kaiming Jin; Qi Sun; Chenchao Zhang; Xiongyong Chen; Zhaoyu Geng (Poultry Science)
Skeletal muscle satellite cells (SMSCs) are critical for postnatal skeletal muscle growth and regeneration. Adiponectin plays a pivotal role in regulating muscle glucose uptake and fatty acid metabolism. However, its function in the proliferation and differentiation of chicken SMSCs remains poorly understood. In this study, we investigated the effects of adiponectin on the proliferation and differentiation of in vitro cultured chicken SMSCs. Our results demonstrated that adiponectin promoted SMSCs proliferation while inhibiting myogenic differentiation and inducing adipogenic differentiation. RNA-seq analysis revealed enrichment of the MAPK signaling pathway, suggesting its potential involvement in the regulation of adiponectin on SMSCs activity. Western blot analysis revealed that adiponectin activated ERK1/2 phosphorylation and inhibited p38 phosphorylation during the process of the inhibition on myogenic differentiation in chicken SMSCs. Furthermore, suppression of ERK1/2 signaling with U0126 or activation of p38 signaling with SSK1 reversed the downregulated expression of myogenic differentiation marker MyHC, MyOD1, and MyOG induced by adiponectin. These findings validated that adiponectin impeded myogenic differentiation through activation of ERK1/2 and inhibition of p38 signaling pathways. Additionally, activation of p38 signaling pathway reduced the increased percentage of EdU-positive cells induced by adiponectin. Collectively, these findings demonstrated that adiponectin impedes myogenic differentiation of SMSCs through activating ERK1/2 and inhibiting p38 signaling pathways, while promoting proliferation by inhibiting p38 signaling pathway.